Analysis and Design of Headless CMS and Graphql in Back-End Development - Yudha Pandu Dewanata; Hadiq Hadiq (Universitas Raharja, 2023)
The application of the website in Village Government can also be useful for informing news or services the community. Therefore, here the author creates an information website for Pondoknongko Village Government. In Pondoknongko Village itself, it does not yet have an information website that is easy to access by admins and users. Indeed, there is already a built-in website from the government, but the admin is still having a hard time adapting and accessing it. There were many deficiencies in the previous website, such as the difficulty of accessing data, and adding and editing data. Therefore, the solution to overcome this problem is to create a website that uses Strapi as a database manager so that it is easy for the admin to manage the data that will be loaded on the information website. The author uses Strapi as a data manager and Graphql as a liaison between the Back end and Front End. This research is also based on a review of the information system used by Pondoknongko Village, the website created has been successfully developed and put to good use by Pondoknongko Village and the community.